2010
DOI: 10.1002/ajim.20920
|View full text |Cite
|
Sign up to set email alerts
|

A 4‐year intervention to increase adoption of safer dairy farming work practices

Abstract: Disseminating information to managers through information channels that they usually consulted was associated with increased reports of getting information and with greater adoption and awareness of safer, profit-enhancing work practices in a high hazard industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…27 Dairy workers, in general, face risks associated with working with large livestock, such as being kicked or crushed by cows or slipping on barn floors. 8,16,27,28 Milking cows requires close contact with cattle and that job in particular results in the greatest injury to workers on dairy farms. 29 Additionally, asthma and chronic bronchitis can result from breathing organic dust from feed.…”
Section: Introductionmentioning
confidence: 99%
“…27 Dairy workers, in general, face risks associated with working with large livestock, such as being kicked or crushed by cows or slipping on barn floors. 8,16,27,28 Milking cows requires close contact with cattle and that job in particular results in the greatest injury to workers on dairy farms. 29 Additionally, asthma and chronic bronchitis can result from breathing organic dust from feed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that health literacy is crucial to protecting health outcomes [35]. Current literature shows that training, fair wages, and health care access are important resources for avoiding poor health outcomes [28][29][30][31][32]55,79]. In Vermont, the work of Migrant Justice has led to the improvement of working conditions in dairy farms throughout the state.…”
Section: Discussionmentioning
confidence: 99%
“…Livestock also pose risk of zoonotic infectious diseases among farm workers [24,25] and exposure to antibiotic-resistant bacteria due to the increased use of antibiotics and antimicrobials in dairy cattle [26,27]. Safety interventions have been shown to be successful in minimizing health risks [3,[28][29][30][31][32], however, many scholars emphasize that few farms have safety expertise, worker safety training, and health insurance, and dairy farming injuries remain common [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…28 Some workforce-related causes of higher rates of occupational morbidity may be amenable to change by improved training, and there are successful programs that have been developed to target food industry workers. 29 One example is severe injuries due to contact with objects or equipment. All food-related industries except for food service had higher rates of severe injuries due to contact with objects or equipment than non-food industries from the same sectors.…”
Section: Discussionmentioning
confidence: 99%